Land Control in The Beach Border Area According to Presidential Regulation No. 51 of 2016 - Riti, Kristina Daido (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Presidential Decree No. 51 of 2016 concerning Coastal Boundaries stipulates regulations regarding land use in coastal areas to protect ecosystems and prevent environmental degradation. This research aims to analyze these regulations in the context of protecting community rights and environmental sustainability. This research analyzes regulations governing restrictions on land ownership in coastal border areas as well as protection mechanisms for traditional and local communities by applying normative juridical methods. The research results show that the coastal border is state land whose use is restricted, except for public interests or conservation with government permission. This regulation provides legal protection for communities through recognition of customary rights, public consultation, as well as compensation and relocation mechanisms. Apart from that, there are administrative sanctions for parties who violate the provisions, including written warnings, fines, and demolition of illegal buildings. Regional governments have the authority to supervise and enforce these regulations, while still considering humanitarian aspects and community rights. Implementation of this policy is expected to balance development and conservation interests, protect coastal ecosystems which are vital for environmental sustainability, and prevent the risk of natural disasters. Thus, this regulation plays an important role in realizing sustainable coastal management and supports the interests of future generations.